Pemetaan dan Strategi Komunikasi Pemasaran Smart Village - Darajat, Deden Mauli (Program Studi Komunikasi dan Penyiaran Islam, 2024)
This article answers the question of how the mapping and marketing strategy of smart villages in Sodong Village, Tigaraksa District, Tangerang Regency, Banten Province. This research is part of Community Service using the method, first, the Smart Village framework, second is SWOT analysis used as a basis for designing strategies and work programs. Internal analysis includes an assessment of strengths and weaknesses. Meanwhile, external analysis includes opportunity and threat factors. Mentoring training in Sodong Village was held on October 26, 2022 at the Parahayangan Agung Bhuwana Raksati Temple Hall (PARABHUSATI). This mentoring focuses on village problems that have previously been analyzed by the Research Team using SWOT analysis as a basis for designing strategies and work programs.Keywords: Mapping, Communication, Marketing, Smart Village, Sodong